Broadening of absorption band by coupled gap plasmon resonances in a near-infrared metamaterial absorber. (20th June 2016) - Cong, Jiawei; Yao, Hongbing; Gong, Daolei; Chen, Mingyang; Tong, Yanqun; Fu, Yonghong; Ren, Naifei
Abstract: We propose a strategy to broaden the absorption band of the conventional metamaterial absorber by incorporating alternating metal/dielectric films. Up to 7-fold increase in bandwidth and ∼95% average absorption are achieved arising from the coupling of induced multiple gap plasmon resonances. The resonance coupling is analytically demonstrated using the coupled oscillator model, which reveals that both the optimal coupling strength and the resonance wavelength matching are required for the enhancement of absorption bandwidth. The presented multilayer design is easily fabricated and readily implanted to other absorber configurations, offering a practical avenue for applications in photovoltaic cells and thermal emitters.